Technology devices: Can it enhance pre-service teachers' teaching? - Syafri, Frimadhona; Wahyuni, Sri (Eureka: Journal of Educational Research, 2022)
The COVID-19 pandemic has resulted in schools being closed around the world. Globally, most children are outside the classroom. As a result, education has changed dramatically, with the advent of typical e-learning, where teaching is done remotely and on digital platforms. These conditions are very demanding on information skills, media, and technology as a solution to these problems. All school activities had been shifted to an online delivery mode, which causes the implementation of teaching practices to be carried out online. This transfer forces pre-service teachers to have different teaching practice experiences. Technological devices are the facilities they use to support online learning. This study aims to describe the implementation and perceptions of pre-service teachers on their teaching practice experiences during the pandemic. Class observations are made on the implementation of English pre-service teachers’ teaching by implementing technological devices in three public junior high schools in Semarang. To evaluate how the teaching and learning process in applying technological devices, the Technological Integrated Matrix (TIM) by Florida Center for Instructional Technology is used as a framework for analyzing the data. TIM provides a framework for describing and targeting the use of technology to enhance learning. Questionnaires and interviews are also administered to obtain information about the pre-service teachers' perceptions of online learning during the pandemic era. Therefore, despite the limitations of its implementation, teaching practice programs tend to form a positive mindset and teaching attitude for pre-service teachers.